2022
DOI: 10.1007/s44155-022-00017-x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices towards COVID-19 among undergraduates during emergency remote learning

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic paralyzes the education sector. To minimize the interruption of teaching and learning, most universities in Malaysia shifted to virtual mode during this unprecedented period of the pandemic. With an ever-increasing number of Malaysians fully vaccinated against COVID-19, the education system is expected to switch back to face-to-face mode this year. It is crucial to assess the knowledge, attitudes, and practices (KAP) of COVID-19 among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“… 16 31 University students in other nations except Bangladesh were found to be more informed and to have better preventive behaviours than those we found for adolescents in our study. 19 However, the majority of the participants reported that mass media (eg, television channels and papers) was the primary source of information regarding COVID-19, which corresponds to previous findings among Jordanian adolescents. 30 This contrasts with recent KAP studies among general Bangladeshi people, that found social media (eg, Facebook) to be the most used source of knowledge regarding COVID-19.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“… 16 31 University students in other nations except Bangladesh were found to be more informed and to have better preventive behaviours than those we found for adolescents in our study. 19 However, the majority of the participants reported that mass media (eg, television channels and papers) was the primary source of information regarding COVID-19, which corresponds to previous findings among Jordanian adolescents. 30 This contrasts with recent KAP studies among general Bangladeshi people, that found social media (eg, Facebook) to be the most used source of knowledge regarding COVID-19.…”
Section: Discussionsupporting
confidence: 77%
“…16 31 University students in other nations except Bangladesh were found to be more informed and to have better preventive behaviours than those we found for adolescents in our study. 19 However, the majority of the participants reported that mass media (eg, television…”
Section: Discussionmentioning
confidence: 99%
“…The rapid spread of COVID-19 globally is attributable to its long incubation period, high transmission rate, and asymptomatic status among carriers. 1 In December 2022, China changed the prevention strategy of COVID-19, with a policy of strict control to open policy, which may lead to the epidemic of diseases. Due to the general susceptibility of new coronaviruses, it is necessary to conduct in-depth research and evaluate the impact of different risk factors on the prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were no differences in how much they cared or the learning state between female and male students in the process of online learning. It has been found that the knowledge, attitudes, and practices (KAP) scores showed no significant difference among female and male students [ 17 ]. Counterparts also revealed that half of female students have higher anxiety states and lower sleep quality, and like people with COVID-19 infection, females had higher rates of anxiety, depression, sleep problems during the pandemic [ 18 ].…”
Section: Discussionmentioning
confidence: 99%